Supporting the University Administration through Innovations: The Roles of a System Analyst - et. al., aburuotu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The roles of the systems analyst remain essential to the backbone of universities in delivering successful administration through technologically powered developments. In recent years, the nature of systems analysts' activities and work environment has changed dramatically, especially in the administration and growth of the university system. This study would look at the functions of a system analyst in assisting university administration. A more machine literate user culture, modern programs, advances, automation of different processes in the university, advancement of existing technology, and a shift toward cooperative systems growth have all led to these changes. The aim of this research is to identify the essential roles of a System Analyst in supporting the education sector through innovation. The goals are to assist line managers, executives, and other key administrators in the university community in using technology and technological advances to drive the structure. The frequency of selected systems analyst behaviors within the context of human relationships experienced by the systems analyst was used to clarify the functions of the systems analyst in this analysis. This paper will also go through how system analysts contribute to the growth of their organizations through proper research, design, production, and implementation. This research would be useful to key stakeholders, line managers, supervisors, executives, and others.